Variability in locomotor activity in a female junior international hockey team - Curran, O.; Neville, R. D.; Passmore, D.; MacNamara, Á. (Journal of Science and Medicine in Sport, 2022)
Objectives: The purpose of this study was to estimate between and within-athlete variabilities, to form threshold values for interpreting changes in locomotor activity in a female junior international hockey team. Design: Thirty-three female international hockey players (age: 20±0.9year; height: 166.1±4.4cm; body mass: 62.5±6.2kg) competed in thirty-four junior international hockey games.. Methods: Data were monitored through global positioning system technology. Locomotor activity was quantified as relative distances covered by players for each quarter at three speed zones (<16km/h, 16-19.9km/h, >20km/h). Data were analysed using linear mixed models, accounting for the fixed effects of position (defenders, n=13; midfielders, n=8; forwards, n=12), game result, type, location, and opposition rank. Variabilities are summarised as coefficients of variation (%CV). Results: Variabilities in athletes` game-to-game and quarter-to-quarter locomotor activity differed substantially between lower (<16km/h) and higher (16-19.9km/h and >20km/h) speed zones. Game-to-game variability of low-speed movement (<16km/h) was 5%; whereas, corresponding variabilities for high- (16-19.9kmh) and very high-speed (>20km/h) running were 22% and 34%, respectively. Within-athlete quarter-to-quarter variability increased for each speed zone, and was greatest for midfielders in low-speed movement and for defenders in high and very high-speed running. Conclusions: The game-to-game variabilities inform thresholds for estimating changes in performance over time. Caution is required when interpreting such data, and coaches should carry out estimates in their specific contexts. Additionally, quarter-to-quarter variabilities in high- and very high-speed running for junior international hockey players outline position specific differences informing training practices to better prepare players for game demands.